Foreign Participation in Emerging Markets' Local Currency Bond Markets - Peiris, Shanaka (IMF Working Papers; Working Paper ;, 2010)
This paper estimates the impact of foreign participation in determining long-term local currency government bond yields and volatility in a group of emerging markets from 2000-2009. The results of a panel data analysis of 10 emerging markets show that greater foreign participation in the domestic government bond market tends to significantly reduce long-term government yields. Moreover, greater foreign participation does not necessarily result in increased volatility in bond yields in emerging markets and, in fact, could even dampen volatility in some instances.